Prenylflavonoids isolated from Macaranga tanarius stimulate odontoblast differentiation of human dental pulp stem cells and tooth root formation via the mitogen‐activated protein kinase and protein kinase B pathways. (30th March 2021) - Nam, S. H.; Yamano, A.; Kim, J. A.; Lim, J.; Baek, S. H.; Kim, J. E.; Kwon, T.G.; Saito, Y.; Teruya, T.; Choi, S. Y.; Kim, Y. K.; Bae, Y. C.; et al.
Abstract: Aim: To identify odontogenesis‐promoting compounds and examine the molecular mechanism underlying enhanced odontoblast differentiation and tooth formation. Methodology: Five different nymphaeols, nymphaeol B (NB), isonymphaeol B (INB), nymphaeol A (NA), 3'‐geranyl‐naringenin (GN) and nymphaeol C (NC) were isolated from the fruit of Macaranga tanarius . The cytotoxic effect of nymphaeols on human DPSCs was observed using a 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay. The effect of nymphaeols on odontoblast differentiation was analysed with Alizarin Red S staining and odontoblast marker expression was assessed using real‐time polymerase chain reaction and Western blot analysis. The molecular mechanism was investigated with Western blot analysis. In order to examine the effect of INB on dentine formation in the developing tooth germ, INB‐soaked beads were placed under the tooth bud explants in the collagen gel; thereafter, the tooth bud explant‐bead complexes were implanted into the sub‐renal capsules for 3 weeks. Tooth root formation was analysed using micro‐computed tomography and histological analysis. Data are presented as mean ± standard error (SEM) values of three independent experiments, and results are compared using a two‐tailed Student's t ‐test. The data were considered to have statistical significance when the P ‐value was less than 0.05. Results: Three of the compounds, NB, INB, and GN, did not exert a cytotoxic effect on human DPSCs. However, INB was most effective in promoting the deposition of calcium minerals in vitro ( P < 0.001) and induced the expression of odontogenic marker genes ( P < 0.05). Moreover, this compound strongly induced the phosphorylation of mitogen‐activated protein (MAP) kinases and protein kinase B (AKT) ( P < 0.05). The inhibition of p38 MAP, c‐Jun N‐terminal kinase (JNK), and AKT substantially suppressed the INB‐induced odontoblast differentiation ( P < 0.001). In addition, isonymphaeol B significantly induced the formation of dentine and elongation of the tooth root in vivo ( P < 0.05). Conclusions: Prenylflavonoids, including INB, exerted stimulatory effects on odontoblast differentiation and tooth root and dentine formation via the MAP kinase and AKT signalling pathways. These results suggest that nymphaeols could stimulate the repair processes for dentine defects or injuries. Abstract :